Improving documentation and use of ultrasound for suprapubic catheter insertions. Issue 1 (21st February 2013) - Day, Nigel
Abstract: The British Association of Urological Surgeons (BAUS) published recommendations for the safe insertion of suprapubic catheters (SPCs) in January 2011. They identified a number of parameters surrounding the insertion and maintenance of catheters that should be identified, implemented and documented on each insertion. One such recommendation was the use of ultrasound, if available and appropriate, to aid insertion and improve patient safety. A previous review of our documentation showed that in 2009, ultrasound imaging was not utilised in any of the 19 SPC insertions. We retrospectively collected data for 36 SPC insertions between April 2010 and December 2011. The information collated was the same as that collected for the BAUS national SPC insertion audit. This quality improvement project identified a significant increase in the use of ultrasound during SPC insertion since 2009 with 17 out of the 36 (47%) cases using this imaging modality. Despite this increase, there was still substantial room for improvement. We also identified some areas of documentation that needed improving, particularly with regard to insertion technique and indication for insertion. As a result, a proforma was designed to be used on each SPC insertion ensuring that all required data is easily identifiable and clearly documented. This proforma is now being used as standard mandatory clinical practice within our Trust.